OPINI AUDIT GOING CONCERN: KAJIAN BERDASARKAN MODEL PREDIKSI KEBANGKRUTAN, PERTUMBUHAN PERUSAHAAN, LEVERAGE, DAN REPUTASI AUDITOR - PRATAMA RUDYAWAN, ARRY; NYOMAN BADERA, I DEWA (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 2 (2009))
The cases of accounting data manipulation that involve big firms, such as Enron and WorldCom, have affected auditor reputation. Enron and 95 other firms received unqualified opinion in the year prior to bankruptcy. This fact raises questions why firms receiving unqualified opinion stop operating. The assessment of going concern has to be delivered by auditor and added into audit opinion.  An auditor is responsible to evaluate whether there is substantial doubt about the entity’s ability to continue its operation for a reasonable period of time. This research aims to investigate the effect of bankruptcy prediction model, firm growth, leverage, and auditor reputation on going concern audit opinion. The result shows that bankruptcy prediction model affects the accuracy of going concern opinion issue. However, the firm growth, leverage, and auditor reputation do not do so.
Keywords: going concern opinion, bankruptcy prediction model, firm growth, leverage, auditor reputation